Stable high-energy proton acceleration with water-leaf targets driven by intense laser pulses - He L.R (PHYSICAL REVIEW RESEARCH, 2025)
Laser plasma acceleration techniques hold promise for generating compact, high-flux relativistic proton bunches. However, the inherent instability of laser-plasma interactions and the requirement for reliable proton source stability often hinder their practical applications. In this paper, we explore the potential of a water-leaf target irradiated by 27 fs laser pulses with energies ranging from 1.1 to 9.9 J and peak intensities spanning from 1020 to 1021W/cm2. We finally conducted a series of 400 shots with a peak power of 300 TW, producing proton energies up to 30 MeV and peak flux beyond 109protonsMeV-1msr-1. These results demonstrate the possibility of long-term, stable, and efficient proton acceleration at high repetition rates, addressing a key challenge in laser-plasma acceleration. © 2025 authors.